PENGARUH PELAYANAN KESEHATAN PENGGUNA BPJS TERHADAP KEPUASAN KONSUMENPADA RUMAH SAKIT UMUM INANTAKOTA PADANG SIDIMPUAN - Winda Angraini Nasution; Imsar Imsar; Atika Atika (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research is entitled "The Influence of BPJS User Health Services on Consumer Satisfaction at the Inanta General Hospital, Padang Sidimpuan City". The aim of this research is to determine the influence of BPJS User Health Services on Consumer Satisfaction at the Inanta General Hospital, Padang Sidimpuan City. The data collection technique uses a questionnaire. which was distributed to respondents using a probability sampling method with a simple random sampling technique using the Slovin formula with a sample size of 100 respondents who were BPJS patients at RSU Inanta, Padang Sidimpuan City. Data analysis techniques include t test, f test, multiple regression and determinant test. The results of the research show that the coefficient of determination (R Square) of the independent variable on the dependent variable is 0.388, which can be interpreted as 3.88% of the independent variable being able to explain the dependent variable. From the results of the partial significant test of the Direct Evidence variable, it is obtained that thitung is 1.412 < 1.99 from ttabel so it can be concluded that the Direct Evidence variable does not have a positive influence on consumer satisfaction. Responsiveness has a positive and significant effect on consumer satisfaction 2.632 with thitung 2.632 > ttabel 1.99 there is a positive influence on consumer satisfaction, guarantee of consumer satisfaction thitung 4.802> ttabel 1.99 has an effect on Consumer Satisfaction. Simultaneous results withFhitung >  Ftabel (20.251> 2.70), meaning that simultaneously direct evidence, responsiveness and guarantee have a positive influence on consumer satisfaction at RSU Inanta Padang Sidimpuan City.